Perinatal risk factors in Tourette's and chronic tic disorders: a lesson from epidemiology - Bruno, Veronica Andrea (2017)
The role of perinatal factors in the pathophysiology of TD/CTD has been repeatedly suggested but never systematically analyzed. The recently published article by Brander et al [1] proposes a relationship between the occurrence of TD/CTD and several adverse perinatal events. The study cohort consisted of all live singleton births over a 30 year period in a single country. Follow up was done over a 40 year period. It included a total of 3,026,861 individuals, 5,597 of which were diagnosed with TD/CTD during the study period. The main results showed that impaired fetal growth, preterm birth, breech presentation and cesarean section were associated with a higher incidence of TD/CTD. A dose–response relationship was also found, by which the higher the number of perinatal events, the higher the risk for TD/CTD. Maternal smoking during pregnancy was also suggested to be associated with the risk of TD/CTD in a dose-response manner; however this could not be verified after sibling comparison analysis.